"We Have to Build Trust": Intimate Partner Violence Risk Assessment with Immigrant and Refugee Survivors. (6th January 2022) - Messing, Jill; Wachter, Karin; AbiNader, Millan; Ward-Lasher, Allison; Njie-Carr, Veronica; Sabri, Bushra; Murray, Sarah; Noor-Oshiro, Amelia; Campbell, Jacquelyn
Abstract: Intimate partner violence (IPV) research highlights unique immigration-related risk factors, abusive tactics, and barriers to seeking help. With the aim of developing practice-informed guidance, data from nine focus groups ( N = 57) were analyzed thematically to examine practitioners' experiences and approaches to risk assessment with survivors of IPV who are immigrants and refugees. Participants noted the importance of fostering relationships and trust in client disclosure and assessment of risk. Participants highlighted using a conversation-based approach; carefully chosen words; and open-ended, indirect, and probing questions to help clients feel at ease and generate information regarding risk. Additionally, practitioners emphasized the importance of conducting risk assessment and client education in concert with safety and service planning. However, safety and service planning must account for variations in context and language, as well as social pressures to keep families together. The adaptation of risk assessments to reflect immigrant experiences is a critical step forward. Nevertheless, listening to practitioners with expertise serving immigrant and refugee IPV survivors and developing additional guidance on how to use risk assessment tools and engage survivors are paramount to expanding relevant and responsive domestic violence services for diverse groups.